Pumpkins from the sky? : a Cobtown story : from the diaries of Lucky Hart - Van Nutt, Julia (New York : Doubleday Books for Young Readers, 1999)
A child's great-great-grandmother's diary reveals the story behind a fallen elm tree, "rescued" pumpkins, and an unusual pig who saves the Cobtown Harvest Festival in 1845.
Keywords: Pigs -- Fiction; Pumpkins -- Fiction